Implementation of an advanced controller strategy to emulate flare trajectories in a hardware-in-the-loop simulation environment - Le Roux, Johan Derik (University of Pretoria, 2022)
Dissertation (MEng (Electronic Engineering))--University of Pretoria, 2022.